DEVELOPED REVERSE PHASE CHROMATOGRAPHIC METHOD FOR ANALYSIS OF PARACETAMOL AND HOMATROPINE METHYL BROMIDE IN RIABASAM TABLET - AL-Tameemi, Maha; M.Abdulkareem, Hawraa; L. Tofah, Mohanad; Abdullh, Mishaal A.; Ziadan, Mothna M.; Mahmood, Mahmood SH. (International Journal of Psychosocial Rehabilitation, 2020)
A developed chromatographic method has been proved in this work to identification Paracetamol and Homatropine methyl bromide in raw material and riabasam tablets. Chromatographic separation system was accomplished using C18 column (250 mm ×4.6 mm) with particle size 5µm. Isocratic elution of mobile phase prepared by dissolve 1.742 g of 1- pentansulfonic acid sodium salt in 750 ml of water, add 220 ml of acetonitrile then the whole solution was adjusted to a pH 3 with 2 M hydrochloric acid, complete to 1000 ml with water. The mobile phase was pumped at a flow rate of 1 ml/min with UV detector at 225nm at ambient temperature at (25±2 C̊) and injection volume as 100 μL. The method was linear over the concentration range of paracetamol and homatropine methyl bromide were 4–30 μg/mL 10-110 μg/mL respectively. The retention time of Paracetamol and Homatropine methyl bromide were found to be 5.4 minutes and 9.7 minutes respectively. Limit of detection and limit of quantification of paracetamol and Homatropine methyl bromide concentrations were found to be (0.442μg/mL and 0.0885 μg/mL) (1.473 μg/mL, 0.295 μg/mL) respectively. The average percentage recoveries of paracetamol were within 100.20 to 102.79% and homatropine methyl bromide were within 98.82 to 100.15%. The suggested procedure has been ratified according to ICH guidelines, validation of method showed it to be particular, durable, accurate and can be adoptable for quality control analysis of paracetamol and homatropine methyl bromide in riabasam tablets.